# Extensions 1→N→G→Q→1 with N=C2 and Q=M4(2).8C22

Direct product G=N×Q with N=C2 and Q=M4(2).8C22
dρLabelID
C2×M4(2).8C2232C2xM4(2).8C2^2128,1619

Non-split extensions G=N.Q with N=C2 and Q=M4(2).8C22
extensionφ:Q→Aut NdρLabelID
C2.1(M4(2).8C22) = C42.371D4central extension (φ=1)32C2.1(M4(2).8C2^2)128,190
C2.2(M4(2).8C22) = C23.8M4(2)central extension (φ=1)32C2.2(M4(2).8C2^2)128,191
C2.3(M4(2).8C22) = C23.15C42central extension (φ=1)32C2.3(M4(2).8C2^2)128,474
C2.4(M4(2).8C22) = C4×C4.D4central extension (φ=1)32C2.4(M4(2).8C2^2)128,487
C2.5(M4(2).8C22) = C4×C4.10D4central extension (φ=1)64C2.5(M4(2).8C2^2)128,488
C2.6(M4(2).8C22) = C42.42D4central stem extension (φ=1)32C2.6(M4(2).8C2^2)128,196
C2.7(M4(2).8C22) = C23⋊M4(2)central stem extension (φ=1)32C2.7(M4(2).8C2^2)128,197
C2.8(M4(2).8C22) = C23⋊C8⋊C2central stem extension (φ=1)32C2.8(M4(2).8C2^2)128,200
C2.9(M4(2).8C22) = C42.372D4central stem extension (φ=1)32C2.9(M4(2).8C2^2)128,205
C2.10(M4(2).8C22) = C42.66D4central stem extension (φ=1)64C2.10(M4(2).8C2^2)128,256
C2.11(M4(2).8C22) = C42.376D4central stem extension (φ=1)64C2.11(M4(2).8C2^2)128,261
C2.12(M4(2).8C22) = C42.69D4central stem extension (φ=1)64C2.12(M4(2).8C2^2)128,264
C2.13(M4(2).8C22) = C42.72D4central stem extension (φ=1)64C2.13(M4(2).8C2^2)128,267
C2.14(M4(2).8C22) = C42.409D4central stem extension (φ=1)64C2.14(M4(2).8C2^2)128,272
C2.15(M4(2).8C22) = C42.410D4central stem extension (φ=1)64C2.15(M4(2).8C2^2)128,274
C2.16(M4(2).8C22) = C42.78D4central stem extension (φ=1)64C2.16(M4(2).8C2^2)128,279
C2.17(M4(2).8C22) = C42.79D4central stem extension (φ=1)64C2.17(M4(2).8C2^2)128,282
C2.18(M4(2).8C22) = C42.417D4central stem extension (φ=1)64C2.18(M4(2).8C2^2)128,285
C2.19(M4(2).8C22) = C42.418D4central stem extension (φ=1)64C2.19(M4(2).8C2^2)128,286
C2.20(M4(2).8C22) = C42.84D4central stem extension (φ=1)64C2.20(M4(2).8C2^2)128,289
C2.21(M4(2).8C22) = C42.86D4central stem extension (φ=1)64C2.21(M4(2).8C2^2)128,291
C2.22(M4(2).8C22) = (C23×C4).C4central stem extension (φ=1)32C2.22(M4(2).8C2^2)128,517
C2.23(M4(2).8C22) = C42.96D4central stem extension (φ=1)32C2.23(M4(2).8C2^2)128,532
C2.24(M4(2).8C22) = C42.97D4central stem extension (φ=1)64C2.24(M4(2).8C2^2)128,533
C2.25(M4(2).8C22) = (C22×C4).276D4central stem extension (φ=1)32C2.25(M4(2).8C2^2)128,554
C2.26(M4(2).8C22) = M4(2)⋊20D4central stem extension (φ=1)32C2.26(M4(2).8C2^2)128,632
C2.27(M4(2).8C22) = M4(2).45D4central stem extension (φ=1)32C2.27(M4(2).8C2^2)128,633
C2.28(M4(2).8C22) = C42.115D4central stem extension (φ=1)32C2.28(M4(2).8C2^2)128,699
C2.29(M4(2).8C22) = C42.128D4central stem extension (φ=1)64C2.29(M4(2).8C2^2)128,730

׿
×
𝔽